Social defence : in the administration of criminal justice - India; Chakrabrti, N. K. (New Delhi : Deep & Deep Pubs., 1999)
In the Indian context; contributed articles
Includes bibliographical references and index
Keywords: Criminal justice, Administration of -- India; Criminal law -- India; Probation -- India